The Role of Digital Contracts in The Insurance Business and Their Relationships on Digital Signature Using PrivyID - Hendra Dwi Prasetya (LAFADZ JAYA Publisher, 2023)
Insurance is an agreement made by the insurer and the insurance cover. In terms of digital agreements or digital contracts in the insurance business, one of the aspects that support business legitimacy is a digital signature (digital signature). One of the digital signature providers is PrivyID. The chosen research method is descriptive analysis. While the type of research in this research is library research conducted through various reading materials. The results of the study state that the implementation of electronic signatures by PrivyID follows the provisions in the ITE Law which require the fulfillment of electronic document security aspects, namely authenticity (authentication), wholeness (integrity), and undeniable (non-repudiation). Privyid has a special insurance product by simplifying policy signing and digitizing workflows, with full legal guarantees, because insurance is a high-complexity business, involving several processes to manage current policies, updated policies, handle customer requests, and process claims. With the rapid growth and changes in the insurance industry, digitizing workflows is necessary to provide efficiency while providing a high level of trust and security in user onboarding.